PENGGUNAAN VIDEO MONOLOG UNTUK MENINGKATKAN KETERAMPILAN BERBICARA UNTUK BIDAN PADA MAHASISWA KAMPUS IBISA PURWOREJO - Taufiq Faruqi, Muhammad (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2023)
ABSTRACT The classic problem that is often faced by students is speaking. This is due to the lack of use of English in everyday life. Therefore, the speaking ability of D3 Midwifery students needs to be improved. This study aims to (1) describe the use of video monologues to improve students' abilities, (2) the appropriate steps in implementing video monologue media, (3) describe student responses to the use of video monologues. Video monologues were used in this study because they were very effective and interesting, fun and did not make students feel bored. The subjects in this study were 43 D3 midwifery students. The object of this research is the use of video monologues, steps, and students' responses to the use of video monologues in learning to speak. The data collection methods used in this study were observation, tests, and questionnaire methods. This research was conducted with research procedures: planning, action, observation, and reflection. Data were analyzed using quantitative descriptive and qualitative descriptive techniques. The results of this study are (1) the achievement of improving students' speaking skills thanks to the use of video monologue media, (2) there are several steps by using video monologues to improve speaking skills. These steps emphasize learning to speak assisted by video monologues. and (3) students gave very positive responses to the use of video monologues in learning English. Keywords: Video Monolog, Speaking, Midwife